The Diagnostic Value of Radiomics-Based Machine Learning in Predicting the Grade of Meningiomas Using Conventional Magnetic Resonance Imaging: A Preliminary Study - Chen, Chaoyue; Guo, Xinyi; Wang, Jian; Guo, Wen; Ma, Xuelei; Xu, Jianguo (Frontiers in Oncology, 2019)
Objective The purpose of the current study is to investigate whether texture analysis-based machine learning algorithms could help devise a non-invasive imaging biomarker for accurate classification of meningiomas, using machine learning algorithms. Method The study cohort was established from the hospital database by reviewing the medical records. Patients were selected if they underwent meningioma resection in the neurosurgery department between January 2015 and December 2018. A total number of 40 texture parameters were extracted from pre-treatment T1C images based on six matrixes. Three feature selection methods were adopted, namely, Distance Correlation, least absolute shrinkage and selection operator (LASSO), and gradient boosting decision tree (GBDT). Multiclass classification methods of Linear Discriminate Analysis (LDA) and Support Vector Machine (SVM) algorithms were employed to establish the classification models. The diagnostic performances of models were evaluated with confusion matrix, based on which the AUCs, accuracy, and Kappa value of models were calculated. Result Confusion matrix showed that the LDA-based models represented better diagnostic performances than SVM-based models. The highest accuracy among LDA-based models was 75.6%, showed in the combination of Lasso+LDA. And the optimal models for SVM-based models was Lasso+SVM with accuracy of 59.0% in the testing group. One of the SVM-based models, GBDT+SVM, was overfitting, suggesting that this model was not suitable for application. Conclusion Machine learning algorithms with texture features extracted from T1C images could potentially serve as the assistant imaging biomarkers for precurgically grading meningiomas.